Tingkat Kepuasan Pengunjung Fasilitas Olahraga: Studi Kasus Gedung Olahraga Samapta Kota Magelang - Alfatin, Nanda Rafif; Bila, Diva Ratna; Aggreani, Difa; Wulandari, Arum; Nugraha, Joko Tri (FIA Unkris Press, 2025)
This study aims to assess visitor satisfaction with the sports facilities at GOR Samapta in Magelang City by examining four key aspects: facility adequacy, accessibility, comfort, and safety. Public sports facilities play a vital role in promoting healthy lifestyles and reflect the quality of public services provided by local governments. A descriptive quantitative approach was employed using a closed-ended questionnaire distributed to 85 randomly selected respondents. Data were analyzed using descriptive statistics with the help of SPSS software. The findings indicate a high level of visitor satisfaction with the services and facilities provided at GOR Samapta. Approximately 63.5% of respondents agreed that the available facilities met their needs, while 55.3% stated that the sports equipment was in good condition. Additionally, 68.2% rated the road access to the facility as good, and 57.6% agreed that it was easily accessible by public transportation. In terms of comfort, 69.4% of visitors found the environment pleasant, supported by good air circulation. Moreover, 65.9% of respondents felt safe while engaging in activities at the facility. This study recommends that local governments and facility managers maintain and enhance the quality of services and infrastructure to sustain and improve public satisfaction. Future research is suggested to adopt a longitudinal or qualitative approach to explore psychological and motivational factors influencing visitor satisfaction and engagement more deeply.